Oyster (Crassostrea gigas) ferritin should be a promising Fe2+ nanocarrier. (15th March 2023) - Li, Han; Xia, Xiaoyu; Wang, Zhenyu; Zang, Jiachen; Du, Ming
Highlights: After adding about 1000 Fe 2+ in vitro, oyster ferritin reached the saturation state. Adding Fe 2+ can improve the storage and thermal stability of oyster ferritin. Heating at 80 ℃ and below does not affect the structure and Fe 2+ content of GF1-1000 Fe 2+ . Abstract: Ferritin, one of the storage forms of iron, which widely exists in all living organisms and shows its potential as functional nanomaterial. In this study, Fe 2+ were added to oyster ferritin (GF1) in vitro until reached experimental saturation state. The structure characterization and monodisperse morphology of ferritin were showed that the protein structure of ferritin did not change significantly after adding Fe 2+ and GF1 with 1000 Fe 2+ (GF1-1000 Fe 2+ ) was selected for subsequent experiments. The storage stability results showed that 11.27 % of the protein remained cage-like structure when GF1-1000 Fe 2+ was stored at 4 °C for 12 days. The thermal treatment results showed that GF1-1000 Fe 2+ still maintained certain structure and activity at 80 °C, and 82.8 % of Fe 2+ was still retained at 80 °C. These experimental results may provide a theoretical basis for the development of novel iron supplement that are non-toxic and highly stable.